The Angular Clustering of WISE-Selected Active Galactic Nuclei: Different Halos for Obscured and Unobscured Active Galactic Nuclei - Donoso, Emilio (2014)
We calculate the angular correlation function for a sample of ~170,000 active galactic nuclei (AGNs) extracted from the Wide-field Infrared Survey Explorer (WISE) catalog, selected to have red mid-IR colors (W1 – W2 > 0.8) and 4.6 μm flux densities brighter than 0.14 mJy). The sample is expected to be >90% reliable at identifying AGNs and to have a mean redshift of langzrang = 1.1. In total, the angular clustering of WISE AGNs is roughly similar to that of optical AGNs. We cross-match these objects with the photometric Sloan Digital Sky Survey catalog and distinguish obscured sources with r – W2 > 6 from bluer, unobscured AGNs. Obscured sources present a higher clustering signal than unobscured sources. Since the host galaxy morphologies of obscured AGNs are not typical red sequence elliptical galaxies and show disks in many cases, it is unlikely that the increased clustering strength of the obscured population is driven by a host galaxy segregation bias. By using relatively complete redshift distributions from the COSMOS survey, we find that obscured sources at langzrang ~ 0.9 have a bias of b = 2.9 ± 0.6 and are hosted in dark matter halos with a typical mass of log (M/M ☉ h –1) ~ 13.5. In contrast, unobscured AGNs at langzrang ~ 1.1 have a bias of b = 1.6 ± 0.6 and inhabit halos of log (M/M ☉ h –1) ~ 12.4. These findings suggest that obscured AGNs inhabit denser environments than unobscured AGNs, and they are difficult to reconcile with the simplest AGN unification models, where obscuration is driven solely by orientation.